2003
DOI: 10.1029/2001jb000820
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary analysis of geomagnetic time sequences from Mount Etna and North Palm Springs earthquake

Abstract: Volcanomagnetic and/or seismomagnetic effects are geomagnetic variations generated before eruptions and/or seismic events. Our aim is to analyze geomagnetic time series to detect the volcanomagnetic and/or seismomagnetic effects among a number of other variations. Two advanced signal‐processing techniques are proposed to analyze the geomagnetic time series. The first technique, called Continuous Wavelet Transform Singularity Analysis (CWTSA), is based on the Continuous Wavelet Transform; the second, called Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In practice, the investigation of radon temporal variability requires nonlinear approaches, as used by Fedi et al [2003] in the analysis of geomagnetic data. Therefore, dispersion around the mean level increases faster (slower) relative to the mean for low (high) Rn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the investigation of radon temporal variability requires nonlinear approaches, as used by Fedi et al [2003] in the analysis of geomagnetic data. Therefore, dispersion around the mean level increases faster (slower) relative to the mean for low (high) Rn.…”
Section: Discussionmentioning
confidence: 99%
“…The statement that Rn time series from Elat are nonlinear has both practical and geophysical implications. In practice, the investigation of radon temporal variability requires nonlinear approaches, as used by Fedi et al [2003] in the analysis of geomagnetic data. Results from methods assuming stationarity and/or linearity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Alperovich and Zheludev [2] analyzed the geomagnetic field data of 1989 Loma-Prieta earthquake (M =7.0) by wavelet packet analysis and stationary wavelet analysis, and they got not only the geomagnetic abnormal signals before the earthquake but also the main frequency band as well as the moving speed of the signal. Some other similar research work [3,4] using wavelet analysis also revealed successfully the geomagnetic abnormal signals before earthquakes. However, the above-mentioned research work mainly focused on the magnitude of abnormal signals.…”
Section: Introductionmentioning
confidence: 67%
“…Such analysis is also well known in geomagnetism [ Alexandrescu et al , 1995], seismics [ Chakraborty and Okaya , 1995; Chamoli et al , 2010b] or in many other scientific frameworks, such as image analysis [e.g., Mallat , 1998]; edge detection [ Mallat and Hwang , 1992]; Holder exponent estimation [ Fedi et al , 2003] and so on. So, methods using the continuous wavelet transform belong to the class of the multiscale methods for the source parameters estimation [ Fedi , 2007].…”
Section: Introductionmentioning
confidence: 99%